Terzo Veneto, Terzo paesaggio. Indagini antropologiche su ambiente e ambientalisti in Veneto - Breda, Nadia (Ri-Vista. Research for landscape architecture, 2015)
A depiction of the Venetian environment and of its transformations, through the voices of Venetian protagonists, analyzed by the anthropological point of view: environment activists, people of the civil society, writers, movie directors, industrials, administrators, urban planners. It is here told the discomfort of the environmental decay, but also the reflection arisen from this context; the texts that tell it; some practices of compensation in the landscape loss (Lilliput gardens, night guardians); new concepts adopted in reading the region (from third Venetian to third landscape). The article ends telling the actions of the “frog groups”, safeguarding animals from slaughters in the roads, to testify a still open conflict around those crucial and sacrificial spots of the landscape, that are the roads.